Immunoprofiling of Chlamydia trachomatis using whole-proteome microarrays generated by on-chip in situ expression - Hufnagel, Katrin; Lueong, Smiths; Willhauck-Fleckenstein, Martina; Hotz-Wagenblatt, Agnes; Miao, Beiping; Bauer, Andrea; Michel, Angelika; Butt, Julia; Pawlita, Michael; Hoheisel, Jörg D.; Waterboer, Tim (Scientific reports, 2018)
Using Chlamydia trachomatis (Ct) as a complex model organism, we describe a method to generate bacterial whole-proteome microarrays using cell-free, on-chip protein expression. Expression constructs were generated by two successive PCRs directly from bacterial genomic DNA. Bacterial proteins expressed on microarrays display antigenic epitopes, thereby providing an efficient method for immunoprofiling of patients and allowing de novo identification of disease-related serum antibodies. Through comparison of antibody reactivity patterns, we newly identified antigens recognized by known Ct-seropositive samples, and antigens reacting only with samples from cervical cancer (CxCa) patients. Large-scale validation experiments using high-throughput suspension bead array serology confirmed their significance as markers for either general Ct infection or CxCa, supporting an association of Ct infection with CxCa. In conclusion, we introduce a method for generation of fast and efficient proteome immunoassays which can be easily adapted for other microorganisms in all areas of infection research.